Pesquisa de Mycobacterium leprae em tatus selvagens da espécie Dasypus novemcinctus no Estado do Espírito Santo - Antunes, João Marcelo Azevedo de Paula (2007)
Introduction: Mycobacterium leprae, was the first agent to be linked to an infectious disease, and leprosy still today an enigmatic disease which is not fully understood. Multibacillary patients are thought to be the main source of M. leprae. Identification of M. leprae is difficult, partly due to the inability of the bacillus to grow in vitro. The natural transmission among nine-banded armadillos in the southern parts of the United States has been described since 1975. This discovery suggested the possibility that the nine-banded armadillo plays a role in the transmission of human leprosy. The search of M. leprae sources is the main point of strategy for leprosy elimination, such as multibacillary patients and environmental sources. It was realized a prevalence study in 69 nine-banded armadillos, Dasypus novemcinctus, from state of Espírito Santo, Brazil, during 2004 to 2005. Objectives: Assess the M. leprae infection in armadillos from D. novemcinctus from state of Espírito Santo through the clinical signs of leprosy found in the necropsy and PCR technique using two set of primers, ML1/ML2 and 18 kDa, such as compare the set of primers. Methods: After anesthesia, the armadillos were weighed, sex was determined, clinical exam was made and samples were collected for PCR. Tissue samples (liver, spleen, brain and lymph nodes) from 65 nine-banded armadillos were collected to looking for natural infection of M. leprae by PCR technique. Results and Conclusion: 95% of the armadillos had at least one clinical sign for leprosy in wild armadillos. Four (6%) animals were positive in conventional PCR. Two animals that were positive in conventional PCR remained positive in Real Time PCR, and confirmed by sequencing. The best method to detect M. leprae was the PCR using the ML1/ML2 set of primers. These results suggest the infection acquired naturally in D. novemcinctus from state of Espírito Santo, Brazil.